289 USE OF SURGICAL RESOURCES AND ASSESSMENT OF RACIAL DISPARITY FOR THE TREATMENT OF NEURAL TUBE DEFECTS IN THE STATE OF CALIFORNIA. (1st January 2006) - Higgins, S.; Friedlich, P.
Abstract : Background: Neural tube defects (NTDs) in neonates often requires surgical closure and/or shunt insertion. Objective: To investigate the relationship between surgical needs, length of hospital stay, and race in neonates with NTD. Methods: NTDs were identified using specific ICD-9-CM codes obtained from the California Office of Statewide Health Planning and Development (OSHPD) for the years 2000 to 2003. ICD-9-CM procedure codes identified cases of closure surgery and/or shunt insertion. Race and ethnicity OSHPD codes were combined to form racial categories. Time between birth and closure surgery/shunt insertion, length of hospital stay, and socioeconomic status (SES) were obtained from the database. Results: Of the 1, 555, 926 infants included in the OSHPD database, 345 were diagnosed with NTD. Of these, 111 were excluded from analyses due to nonspecified defect, lack of racial data, or inconsistent procedural codes. Sample size for analysis was 234. Analysis of variance showed differences between racial groups for shunt insertion ( p = .003), closure surgery ( p < .001), time to closure surgery (p < .001), length of stay (p = .025), and SES (p = .002). Whites (71/177) underwent closure surgery more than blacks (0/5), Asian/Pacific Islanders (1/13), and Hispanic-others (2/35) (p = .024; p = .006; p < .001, respectively). Whites (32/177) received shunts more than Asian/Pacific Islanders (0/13) and Hispanic-others (0/35) (p = .032, p = .004, respectively). Mean length of hospital stay was greater for whites (7.6 days) than for Asian/Pacific Islanders (2.5 days) and Hispanic-others (2.4 days) (p = .044, p = .004, respectively). Whites had higher SES (63/176) than blacks (0/5) and Hispanic-others (6/35) (p = .045; p = .015, respectively) and lower SES than Asian/Pacific Islanders (10/13) (p = .001). Partialing of dependent variables for mediational effects of SES did not significantly alter racial group-dependent variable relationships. Conclusion: The data indicate racial differences in the use of surgical resources for NTDs. Whites more heavily utilized surgical resources, with longer hospital stays and greater proportions undergoing closure surgery/shunt insertions. Defect severity was not included in the OSHPD database and may mediate the relationships found in this study.